500 years of breeding in the Carthusian Strain of Pura Raza Español horse: An evolutional analysis using genealogical and genomic data. (7th August 2021) - Poyato‐Bonilla, Julia; Laseca, Nora; Demyda‐Peyrás, Sebastián; Molina, Antonio; Valera, Mercedes
Abstract: The Carthusian horse is a Pura Raza Español (PRE) strain (CS), bred as a closed population since its creation more than 500 years ago. The aim of this study was to analyse for the first time its population structure and situation of variability combining both genealogical (GEL) and genomic (GEN) data. The GEL data comprised 348, 429 pedigree records (56, 105 CS horses), while the GEN analysis included the high‐density genotypes (670, 804 SNPs) of 287 horses. Pedigree completeness demonstrated its accuracy, showing a good correlation of GEL ( F ) and GEN (FROH ) inbreeding coefficient in the case of PRE subpopulations partially related and non‐related to Carthusian strain (0.68) but a lower value in the 100% Carthusian horses (0.42), due to the high weight of founders not detected by GEL analysis. GEN (PCA, AMOVA, and Admixture) and GEL analysis showed a good differentiation of subpopulations, but also a high level of introgression of the CS in the breed during past decades. A recent change in this trend was noteworthy, with a considerable reduction in CS variability and a genetic bottleneck (effective population sizes of 31.57 and 30.20 in GEL and GEN analysis, respectively, in last generation). The PRE has maintained its variability, and a considerable difference in estimated Ne by GEL (60.77) and GEN (188.0) data was observed. Using two sources of complementary information, it was found the existence of an ancient PRE strain with a unique genetic landmark, practically free from the influence of other equine populations.